Penatalaksanaan Holistik pada Pasien Laki-Laki Dewasa dengan Penyakit Paru Obstruktif Kronik melalui Pendekatan Kedokteran Keluarga - Renti Kusumaningrum Samosir; Dian Isti Angraini (Majority, 2020)
Chronic obstructive pulmonary disease (COPD) is a slow progressive and irreversible or partially irreversible lung disease. Risk factors for COPD include exposure to cigarette smoke, air pollution, exposure to dust and smoke in the work environment. The goal of COPD management is to reduce symptoms, prevent acute exacerbations and decreased lung function. This study is a case report with data obtained through history taking (autoanamnesis and alloanamnesis), physical examination and home visits to complete family data, psychosocial and environmental data. Patient Mr. J 49-year-old diagnosed with COPD. Patients have aspects of internal risk in the form of a history of smoking for 16 years, lack of patient knowledge about the illness, feeling bored and stressed out of not working. The external risk aspects are in the form of lack of family knowledge about the disease and its complications as well as curative treatment patterns, a history of vehicle smoke exposure at work for 27 years. Home visits were done three times to intervene in the form of education and counseling in patients and families about the causes, risk factors, clinical symptoms, prognosis, to prevent complications. In the evaluation, it was found that the patient had shown improvement. The diagnosis and management of these patients has been done holistically, patient centered, family approached, community oriented and based on several theories and current research. In the process of behavior change, Mr. J has reached the trial stage for COPD diet and physical exercise after being given an intervention.